Panorama de la evaluación e inspección educativa en Andalucía - Barea Romero, Cristóbal (Avances en Supervisión Educativa, 2023)
A panoramic view of educational evaluation in Andalusia is carried out from the perspective of educational inspection. After establishing the conceptual framework and reviewing the recent evolution of the main actions in which the education inspection has participated in the educational evaluation, a description of the current situation is developed, focusing on the evaluation of centers, to finally provide some conclusions and proposals.
Keywords: Education Inspection; Assessment